Sequence analysis of temperature-sensitive mutations in the Saccharomyces cerevisiae gene CDC28. - Lörincz, A T (1986)
Eleven independently isolated temperature-sensitive mutations in the cell division cycle gene CDC28 were mapped with respect to the DNA sequence of the wild-type gene and then sequenced to determine the precise nature of each mutation. The set yielded six different point mutations, each of which predicts a single amino acid substitution in the CDC28 product. The positions of the mutations did not correlate in any obvious way with observable biological characteristics of the mutant alleles. When the positions of substitutions were collated with a predicted secondary structural analysis of the CDC28 protein kinase, they were found to correlate strongly with probable regions of structural transition.